สัดส่วนร่างกายและความสามารถในการทำงานโดยใช้แรงของคนงานชายที่ทำงานกสิกรรมในจังหวัดขอนแก่น - พรเทพ ขอขจายเกียรติ (จุฬาลงกรณ์มหาวิทยาลัย, 1988)
This study was to develop a mathematical model to predict a physical work capacity (PWC) value of agricultural male works in Khon Kaen Province from age, heart rate at a work load and other independent variables based on a 0.05 significant level. The physical work capacity, static muscle strength of back, arm, standing leg, shoulder and composite muscle were also compared among 5 age ranges, i.e., 20-24, 25-29, 30-34, 35-39, and 40-49 years. Forty-two body dimensions were measured and recorded. It was found that the physical work capacity was highest for 20-29 year old group of workers and declined with ages. This complies with other foreign researchers. The standard error of estimate, the sum of the squares of the errors and correlation coefficient of the PWC predictive model were 9.38%, 7.44, and 0.90, respectively. The validation of this model using another group of subjects gave the sum of the squares of the errors was 1.47. A mathematical model was also developed to estimate an oxygen uptake values at a work load using ventilation volume, heart rate, and age as independent variables. It was found that the standard error of estimate, the sum of the squares of the errors and correlation coefficient of this equation were 3.07%, 4.41, and 0.95, respectively. The model validation was performed and the sum of the squares of the errors was 1.85. The standard deviation of 42 body dimensions were in a range of 0.5 to 7.7 centimeter. Static muscle strength of back, standing leg, shoulder, and composite muscle for each age group were not significantly different but arm strength of 35-39 years old workers are significantly higher than those of 20-24 and 40-49 years old workers. This was probably because agricultural, male workers in this age range were working as vegetable garden workers in which arms were mainly utilized. It could be concluded that the garden work type provided significantly effect on arm strength than cropping and paddy work types